(untitled) (Arfannur: Journal of Islamic Education, 2024)
The Merdeka Curriculum has been tested in 2,500 Sekolah Penggerak (driving schools). Not only in driving schools, this curriculum was also launched in other schools. According to data from the Ministry of Education and Culture, Research and Technology, to date, there are 143,265 schools that have used the Independent Curriculum. This number will continue to increase as the Independent Curriculum begins to be implemented in the 2022/2023 school year at the kindergarten, elementary, middle and high school levels. In this research, the method used is a qualitative method using a descriptive approach. This research is a type of research that aims to describe and analyze systematically, factually and precisely or describe phenomena, events, social activities, attitudes, beliefs, perceptions, and thoughts of people individually and in groups. Implementation is an activity process carried out in a planned manner based on a guideline and carried out based on achieving goals in an activity. Implementation cannot run well without linkages with other objects. Learning motivation is a condition within an individual that causes someone to want to carry out learning activities to achieve learning goals.